Paulo Freire: Critical, Humanist and Liberating Education (Critical Reflections on Indonesian Education) - Mahur, Yeremias; Riyanto, Yatim; Roesminingsih, Erny (Universitas Malikussaleh, 2019)
This thesis presents about education concept of Paulo Freire about the education which are critical, humanist, and free. This education concept is Freire's opinion towards traditional education practice. Paulo Freire sees that education reality is an oppression reality. That is reflected in two things in the in education praxis; first, hegemony in education, which is a relation between teacher and student that is not based on humanity relation, but between a sovereign and subordinate. Teacher becomes the dominant subject in the relationship and the student is just an object. Whereas, both teacher and student are the learning subject. Second, education in bank style. Education in this model places student as an empty bottle that must be filled by the teacher. Seeing that condition, Freire proposes different concept and school praxis. That is critical education, humanist, and independence as the writer says in this thesis. The result of that education process will create a mindful human being. Freire calls it consientization. This thesis will also examine the coherence with education in Indonesia.